FECUNIDITY AND TYPE SPAWNING EEL, Electrophorus electricus (LINNAEUS, 1766) (OSTEICHTHYIES: GYMNOTIFORMES: GYMNOTIDAE) AREA OF ENVIRONMENTAL PROTECTION - APA - RIVER CURIAÚ, MACAPÁ-AP - SÃ¡-Oliveira, JÃºlio CÃ©sar (2012)
This study investigated the fecundity and spawning type of electric fish Electrophorus electricus of the Environmental Protection Area - APA Curiaú River, Amapá - Macapá. The analyzes were performed from 96 samples of fish collected from March 2006 to February 2007. Analysis of the annual cycle of gonadal maturation stages, macro and microscopic examinations of the gonads, verification and counting of the diameters of oocytes were performed. The number of oocytes is related to a body dimension (length)and the Total Weight (g) was adjusted to a linear regression. The results revealed that spawning is complete and synchronous type, occurring in early winter (January-February). Fecundity, estimated ranged from 1730 to 3063 vitellogenic oocytes. The fecundity was positively correlated with the total length and total body weight, increasing proportionally with the size of Electrophorus electricus.Keywords: reproductive biology; Amapá; maturation stages; Brazil.